Neoadjuvant chemotherapy reduces the expression rates of ER, PR, HER2, Ki67, and P53 of invasive ductal carcinoma. Issue 2 (January 2019) - Peng, Jian-Heng; Zhang, Xiang; Song, Jun-Long; Ran, Liang; Luo, Rong; Li, Hong-Yuan; Wang, Yong-Hong
Abstract : Abstract: To analyze whether neoadjuvant chemotherapy (NAC) changes the expression rates of invasive ductal carcinoma (IDC) markers: estrogen receptor (ER), progesterone receptor (PR), human epidermal growth factor receptor 2 (HER2), Ki67, and P53. This was a retrospective study of 112 IDC patients who underwent NAC (docetaxel+epirubicin/pirarubicin+cyclophosphamide) but without pathological complete response (pCR) in 2012 to 2013 at the First Affiliated Hospital of Chongqing Medical University. The IDC subtypes and tumor protein markers were analyzed by immunohistochemistry (IHC). Specific changes in tumor protein markers before/after NAC were compared. The decrease in the positive rate of Ki-67 was the most significant, from 75.9% before NAC to 41.1% after NAC ( P  < .001). The positive rate of HER2 decreased from 42.0% before NAC to 32.1% after NAC ( P  = .04). The positive rate of ER decreased from 66.1% before NAC to 56.2% after NAC ( P  = .04). Increased number of metastatic lymph nodes ( P  = .006) and body mass index (BMI) ( P  = .028) seemed to be related to conversion of PR (positive to negative). There was statistical association between the Ki-67 (positive to negative) with the age greater or equal to 50 ( P  = .015). The BMI greater or equal to 24 ( P  = .021), age greater or equal to 50 ( P  = .047), and blood type A ( P  = .038) were independently associated with conversion of P53 (positive to negative). The BMI greater or equal to 24 ( P  = .004), number of metastatic lymph nodes greater or equal to 1 ( P  = .029) and TNM stages I–II ( P  = .008) were statistically associated with change of HER2 (positive to negative). In patients without pCR, NAC leads to changes in Ki-67, HER2, and hormone receptor (HR) expression. Age, BMI, number of metastatic lymph nodes, and TNM stage are associated with some changes of markers.